Impact of Environmental Sanitation and Hygienic Practices on Nutritional Status of Lodha Women and Children of West Bengal, India - Prasanta, Sabud; Tarapada, Ghosh; Arup, Dhar; Sarnali, Dutta; Samiran, Bisai; Sujata, Maiti Choudhury (International Journal of Nutrition, 2020)
Aim To assess the sanitation and hygienic practices of women and its effects on the nutritional status of the mother and preschool children of the Lodha tribal community in two districts of West Bengal. Methods A cross-sectional study was conducted during November, 2014 - December, 2018 of 941 Lodha mothers and 1043 of their preschool children in Paschim Medinipur and Jhargram districts. All information was collected by using KAP questionnaire following interview and group discussion. Mother nutritional status was assessed based on body mass index (BMI) and mid upper arm circumference (MUAC). A child was classified as underweight, stunting and wasting as weight-for-age, height-for-age and weight-of -height Z-score below -2 standard deviation of WHO standard. Results This study found 35% of the households used safe drinking water. Almost 97.2% of the mother had the low hand wash score and about 67.1% of them had an average WaSH score. Overall, 41.6% and 1.6% mothers were suffered from undernutrition (BMI <18.5 kg/m2) and overweight/obesity (BMI≥25kg/m2). Whereas, 48.9% women were undernourished based on MUAC<22.0cm. Moreover, the overall prevalence of wasting, stunting and underweight of preschool children was 31.9%, 62.1% and 61.3%, respectively. The WaSH score of family was significantly associated with child stunted and underweight. Conclusion There is a good association between poor household WaSH practices with child undernutrition and morbidity. Hence, there is an urgent need to develop the comprehensive knowledge, attitude and practice (KAP) guidelines in their language to educate them about appropriate water storage, retrieval methods, sanitation and hand washing practices.
Keywords: Lodha; Sanitation; Hygiene; Malnutrition; Stunted; Underweight; India